Outils d'analyse des contenus mathématiques à enseigner au lycée et à l'université - Robert, Aline (Recherches en didactique des mathématiques, 1998)
Abstract In this article, we propose some tools for the analysis of mathematical notions which are taught to students of more than 15-16 years old. Our goal is to take into consideration the complexity and the specificity of the notions within the context of the curricula. We also develop some institutional expectations and hypotheses on ... Lire la suite